Solubility enhancement of glimperide: Development of solid dispersion by solvent melt method, characterization and dosage form development - Kamla Pathak; Suchitra Kaushik (Mazandaran University of Medical Sciences, 2017)
The aim of the present work was to develop immediate release dosage form of the solid dispersion of glimperide (GLIM) for potential enhancement in the bioavailability. The solid dispersions of GLIM were prepared with PEG6000, PVP K30 and Poloxamer 188, in 1:1, 1:3 and 1:5 %w/w ratio by using solvent wetting and solvent melt method. The in vitro dissolution parameters (%DE10min, %DE30min, %DE60min, T50% and DP30) were used to select the optimized solid dispersion that was characterized by IR, PXRD, DSC and SEM. The optimized solid dispersion of GLIM (GSDSM3) was used as drug component for immediate release (IR) tablets that were evaluated for physical and pharmacopoeial parameters. The in vitro drug release studies identified G4 as the optimized tablet with a cumulative drug release (CDR) of 99.34% in 30 min in phosphate buffer, pH 7.4. The CDR was higher than the marketed tablet (91.15%, Amaryl®, Sanofiaventis), However, the f1 and f2 were 10.6 and 52 respectively, which confirmed similarity of the dissolution profile(s). Accelerated stability studies confirmed stability up to 6 months at 40°C/75% condition in the HDPE bottle pack.